(untitled) (Revista Científica Ciencias Naturales y Ambientales, 2016)
The aim of the current study, is to determinate the impact of the application of the learning strategy called “Inverted Classroom” and the student’s learning reflected quantitatively in the academic performance. It is founded on the constructivism theory by Jean Piaget, in the techniques focused on the personalized education of the meaningful learning theory by David Ausubel, the educator’s strategies for meaningful learning by Fridda Díaz Barriga. It was applied an experimental research. It was created a website where it was published multimedia resources such as videos, pictures, text, elaborated with the ICT tools, Google Sites, Google Drive and Youtube. The results revealed that the application of the Inverted Classroom strategy had good acceptance by students, It helped to improve the motivation and interaction levels between students and educators, reinforcing and improving their academic performance reflected on the grades which revealed a high percent of students with excellent and the whole class passed directly the subject. In conclusion, the application of the learning strategy had a positive impact in the academic performance, moreover of supporting the accomplishment of the proposed standards in the academic innovation program of the University of Guayaquil.